2022
DOI: 10.3390/fishes7050270
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of the Impact of Climate Change on Performance of Fish Hatcheries in Bangladesh: An Empirical Study

Abstract: The impacts of climate change (CC) on all spheres of human life are evident worldwide. Fish is the premier protein source, and its production in Bangladesh is mainly dependent on hatchery-based seed production. However, hatchery productivity is disrupted every year due to CC. This study assesses the impacts of CC on fish seed production in hatcheries from the perspective of hatchery owners. A semi-structured questionnaire survey was conducted with 60 hatchery owners in five sub-districts (Trishal, Mymensingh S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…The changes in growth and water quality parameters because of climatic changes can also be a potential issue regarding farm production because of the industry's dependency on natural culture units. For instance, temperature-induced changes in reproductive performance can affect the production of seeds in hatcheries (Siddique et al, 2022). Although climatic changes are somewhat invincible, the construction of dams, embankments, and dikes; farming fast-growing fish species; and crop rotation can be adopted to deal with the climatic extremes (Ahmed & Diana, 2016).…”
Section: Climate Changementioning
confidence: 99%
“…The changes in growth and water quality parameters because of climatic changes can also be a potential issue regarding farm production because of the industry's dependency on natural culture units. For instance, temperature-induced changes in reproductive performance can affect the production of seeds in hatcheries (Siddique et al, 2022). Although climatic changes are somewhat invincible, the construction of dams, embankments, and dikes; farming fast-growing fish species; and crop rotation can be adopted to deal with the climatic extremes (Ahmed & Diana, 2016).…”
Section: Climate Changementioning
confidence: 99%
“…Siddique et al (2022a) reported that climate change such as temperature fluctuation, erratic rainfall, and solar radiation is becoming a major concern of hatchery owners for the productivity of fish hatchery. Climate change due to geographical location of Bangladesh can impact the embryonic development and impair maturation and breeding performance of broodstock (Siddique et al, 2022b).…”
Section: Disease Outbreaks and Use Of Chemicals And Drugs In Hatcheriesmentioning
confidence: 99%
“…Climatic variables, such as temperature and rainfall, and changes in water quality parameters, such as dissolved oxygen (DO), pH, and alkalinity, significantly affect embryonic and larval growth [ 13 , 14 , 15 ]. According to a recent study [ 16 ], fish hatcheries including hatcheries of stinging catfish are being negatively affected by various climatic changes, such as changes in air and water temperatures, rainfall, and sunlight intensity, as well as frequent natural disasters, resulting in disruption of hatchery production with poor quality fry. Among the different climatic and water quality parameters, temperature is a fundamental factor that influences other parameters in various ways to affect broodfish reproductive processes, such as growth, maturation, ovulation, breeding, embryonic development, hatching of eggs, and larval and juvenile growth and survival [ 17 ].…”
Section: Introductionmentioning
confidence: 99%